2010
DOI: 10.1051/0004-6361/201014324
|View full text |Cite
|
Sign up to set email alerts
|

Detecting emission lines withXMM-Newtonin 4U 1538–52

Abstract: Context. The properties of the X-ray emission lines are a fundamental tool for studying the nature of the matter surrounding the neutron star and the phenomena that produce these lines. Aims. The aim of this work is to analyse the X-ray spectrum of 4U 1538−52 obtained by the XMM-Newton observatory and to look for the presence of diagnostic lines in the energy range 0.3−11.5 keV. Methods. We used a 54 ks PN & MOS/XMM-Newton observation of the high-mass X-ray binary 4U 1538−52 covering the orbital phase between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 35 publications
4
25
0
Order By: Relevance
“…The X-ray spectrum (Robba et al, 1992) displays two cyclotron absorption features (Clark et al, 1990;Robba et al, 2001;Rodes-Roca et al, 2009). Emission lines from an extended ionised region have been detected during eclipses (Rodes-Roca et al, 2011). Small spin-up and down have been detected .…”
Section: Discussionmentioning
confidence: 97%
“…The X-ray spectrum (Robba et al, 1992) displays two cyclotron absorption features (Clark et al, 1990;Robba et al, 2001;Rodes-Roca et al, 2009). Emission lines from an extended ionised region have been detected during eclipses (Rodes-Roca et al, 2011). Small spin-up and down have been detected .…”
Section: Discussionmentioning
confidence: 97%
“…thanks the Matsumae International Foundation Research Fellowship. (Clark 2000), BeppoSAX (Robba et al 2001), XMM-Newton (Rodes-Roca et al 2011), INTEGRAL (Hemphill et al 2013), and Suzaku (Hemphill et al 2014). The X-ray characteristics derived from these analyses suggest that the mass accretion onto the neutron star is consistent with a spherically symmetric stellar wind from the companion star (Mukherjee et al 2006).…”
Section: Introductionmentioning
confidence: 85%
“…Previous works in this direction have been carried out for only one or two orbits (Makishima et al 1987;Robba et al 2001;Mukherjee et al 2006;Rodes-Roca 2007) or for a shorter orbital phase (Rodes-Roca et al 2011). We obtained orbital phaseresolved spectra of the HMXB pulsar 4U 1538−52, accumulating the 60 s duration scans into six ∼0.5 day orbital phase bins outside of eclipse (Nakahira et al 2012;Doroshenko et al 2013;Islam & Paul 2014).…”
Section: Orbital Phase-resolved Spectramentioning
confidence: 99%
“…An absorption feature at ∼22 keV in the spectrum of 4U 1538−522 was discovered and identified as a CRSF by Clark et al (1990); another absorption feature at ∼50 keV was observed by Robba et al (2001) and identified as the harmonic of the 22 keV CRSF by Rodes-Roca et al (2009). The spectrum also features a 6.4 keV emission feature, identified as the Fe Kα line (Makishima et al 1987), as well as other emission lines in the ∼1-3 keV and ∼6-7 keV range (Rodes-Roca et al 2010). Until now, the parameters of the cyclotron line have not displayed any detectable correlation with luminosity; however, conclusions in this area have been difficult to arrive at due to previous work using a mix of different empirical models for the continuum and the cyclotron line shape, with Clark et al (1990), Mihara et al (1998), and Rodes-Roca et al (2009) using Lorentzian-shaped line profiles for the CRSF and Coburn (2001), Robba et al (2001), and Hemphill et al (2013) adopting Gaussian profiles.…”
Section: Introductionmentioning
confidence: 97%